Host country-foreign investor bargaining power and investment incentive provisions in multilateral investment agreements - Mash, R (University of Oxford, 2000)
The paper is concerned with foreign investment in developing countries and the incentives offered to attract that investment in relation to the use of a possible future multilateral investment agreement as a commitment device over incentive levels. The existing literature has identified two sources of benefit from such commitment, firstly to avoid time inconsistency problems whereby incentives are less effective than otherwise because investors fear that they may be reduced once sunk costs have been incurred, and secondly to avoid excessive competition for foreign investment. This paper demonstrates a third benefit from commitment which arises from low host country bargaining power when negotiating incentive levels with foreign investors. If bargaining power is low, incentives agreed under bargaining will be generous to the investor and host country welfare will be lower than otherwise. It is shown that this consequence of low bargaining power may be avoided if host countries can commit themselves in advance to provisions that limit the incentives they may subsequently agree with foreign investors. It is argued that provisions of this kind should be optional from a host country perspective since those with low bargaining power will gain from them but those with high bargaining power would not.